Is ethics in the traditional meaning of the word possible after Heidegger and Levinas? - Moń, Ryszard (Filozofia Chrześcijańska, 2009)
The author tries to answer the question whether thinking is possible as a type of knowledge about human behaviour. To this end, he compares two thinkers, who, while differing considerably from one another, are similar in that they reject the traditional philosophy of existence, and use language with multiple meanings. Heidegger considered ethics as something of fundamental importance, but differing from ethics as knowledge, or as normative science. Levinas, on the other hand, believed ethics was the first philosophy, but did not treat it as normative. He argued that ethics was not cultivation of good, nor even a system of values, but a relationship with others. Heidegger criticized traditional ethics and morality, treating them as immature, juvenile even. Nevertheless, there is something in his writings that suggests what he had in mind was the necessity of existence. The ethics criticized by Heidegger or by modern French anti-humanists as well as Levinas reemerges in the form of humanities, as a discipline which puts man in the centre of the universe and defines actions that are appropriate for him. Shouldn’t we, however, following the train of Kant’s thought on the role of judgment, affirm the ontological difference Heidegger talked about? Since Kant accepted valuation of beauty, one can hazard a guess there exists a certain minimum of substantiation; if not of moral truth, then at least of substantiation at the level of meaning. Subjectivity must be shown as the power to create meaning, and thus to take moral action. Ethics after Heidegger still seems to be possible.